Pemberdayaan Program Kajian Fikih di Mushola Darul Ihsan Melalui Media Digital - Amira Rohaini; Ahmad Syafi'i Sulaiman Jamrozi (Social Science Academic, 2025)
This research examines the use of digital media in empowering fiqh study programs in Mushola Darul Ihsan Dukuh Tengah RT.001/RW.001, Desa Nambangrejo, Kec. Sukorejo, Kab. Ponorogo. The aim of this empowerment is as a form of optimizing existing resources so that they can face global challenges and increasingly rapid technological developments. In the era of information technology, the use of digital platforms has become strategic to expand the reach and increase the effectiveness of fiqh learning. . The method used is Asset Based Community Development (ABCD). The research results show that the use of digital media such as mobile applications, video streaming, and social media can increase accessibility, interactivity, and personalization in the study of jurisprudence. Challenges faced include the need to adapt materials for digital formats and increase participants' digital literacy. In conclusion, the integration of digital media in fiqh study programs has the potential to significantly increase public participation and understanding of Islamic law, with recommendations for developing quality digital content and training in the use of technology for teachers.